2018
DOI: 10.1155/2018/3606970
|View full text |Cite
|
Sign up to set email alerts
|

Primary CNS Lymphomas: Challenges in Diagnosis and Monitoring

Abstract: Primary Central Nervous System Lymphoma (PCNSL) is a rare neoplasm that can involve brain, eye, leptomeninges, and rarely spinal cord. PCNSL lesions most typically enhance homogeneously on T1-weighted magnetic resonance imaging (MRI) and appear T2-hypointense, but high variability in MRI features is commonly encountered. Neurological symptoms and MRI findings may mimic high grade gliomas (HGGs), tumefactive demyelinating lesions (TDLs), or infectious and granulomatous diseases. Advanced MRI techniques (MR diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 133 publications
(148 reference statements)
3
122
0
1
Order By: Relevance
“…Primary Central Nervous System Lymphoma is a rare extranodal NHL, involving the brain, eye, leptomeningitis, and rarely spinal cord. [ 3 , 14 ] The diagnosis of CNS lymphoma is always challenging. Presently, it is mainly based on clinical characteristics, imaging, CSF analysis, and brain biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Primary Central Nervous System Lymphoma is a rare extranodal NHL, involving the brain, eye, leptomeningitis, and rarely spinal cord. [ 3 , 14 ] The diagnosis of CNS lymphoma is always challenging. Presently, it is mainly based on clinical characteristics, imaging, CSF analysis, and brain biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Flanagan et al reported that spinal cord 18 F-FDG-PET/CT hypermetabolism in patients with active myelopathy was much more common than in ammatory myelopathies (12). PCNSL has a strong uptake of 18 F-FDG, while the 18 F-FDG uptake is not obvious in non-enhancing lesions on MRI (13).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body 18 F-FDG-PET/CT can be performed to detect sys- temic lymphoma before corticosteroid administration in a PCNSL-suspected patient who has difficulty undergoing brain biopsy, as systemic involvement of DLBCL is found in 7% of PCNSL-suspected patients at initial diagnosis [11]. However, studies on the usefulness of 18 F-FDG-PET/CT in differentiation of PCNSL from IDD is lacking [12]. The key radiologic features that help distinguish PCNSL with spinal cord involvement from IDD are: (1) multifocal intramedullary lesions with brain lesions [5]; (2) involvement of the conus medullaris or cauda equine [5]; (3) persistent Gd-enhancing intramedullary lesions for over 8 weeks [5]; (4) persistent, contiguous Gd-enhancing MRI lesions along the ventricular regions and spinal leptomeninges [4]; and (5) intraparenchymal tadpole-like enhancing lesions, which may be helpful in suspected PCNSL cases.…”
Section: Discussionmentioning
confidence: 99%